Cuentas por cobrar de la empresa INTEAUTO - ECU S.A. de la ciudad de Guayaquil, en los periodos 2022-2023 - Franco Alvario, Nathaly Liliana (2024)
The case study "Accounts Receivable of the company INTEAUTO - ECU S.A. in the city of Guayaquil for the periods 2022-2023" analyzes the management of accounts receivable and its impact on financial stability. Deficiencies in credit policies, account monitoring, and communication with customers resulted in an increase in bad debts and a prolonged collection cycle, affecting the company's liquidity and solvency. Justified by the need to improve these areas, the objective is to analyze the management of accounts receivable through accounting review and the application of financial indicators. The methodology includes financial statement analysis, interviews with the manager, and policy review. The results show a 19.40% increase in accounts receivable from customers and a 20.91% decrease in notes receivable, while total assets increased by 309.04%. The accounts receivable turnover improved significantly, reducing the average collection period from 287.33 days in 2022 to 108.95 days in 2023. The conclusions emphasize the importance of implementing strict credit policies, strengthening account monitoring and collection, and optimizing liquidity management to maintain the company's financial stability.